Totally implantable venous access port infection with Listeria monocytogenes: 2 case reports at a tertiary center and literature review - Christian Haddad; Rindala Saliba; Racha Ibrahim; Jacques Choucair (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
Listeria monocytogenes infection in humans is mostly asymptomatic in immunocompetent patients. It rarely can cause self-limiting febrile gastroenteritis, bacteremia, meningoencephalitis, and maternal-neonatal infections. The latter three manifestations are the most common, especially among immunocompromised patients. We present two cases of Listeria monocytogenes bacteremia in cancer patients, a 79-year-old man and a 70-year-old woman in whom the source of bacteremia was identified to be the implantable venous access port (TIVAP). In both cases, the TIVAP has been removed after "positive control cultures the following readmission to the hospital despite targeted therapy with ampicillin and gentamicin". Removal of TIVAP was warranted to control the infection.